Correlation between Fatique and Stress among Female in Caring for the Elderly at Hospitals - Roxsana Devi Tumanggor; Anna Kasfi; Nurbaiti Nurbaiti; Diah Lestari Nasution (Jurnal Keperawatan Padjadjaran, 2021)
Background: Studies showed that the caregiving process has an impact on physical and psychological health, such as stress and fatigue. Purpose: This research aims to analyze the correlation between fatigue and stress in female caregivers caring for the hospitalized elderly in Medan, Indonesia. Methods: This is a correlational study with a cross-sectional approach. Data collection was conducted from March to October 2020 and 42 caregivers participated. The data analysis was performed to analyze for frequency distribution and the Pearson correlation test was used to measure the strength of the correlation between variables. Results: It was reported that 47.5% of female caregivers were in the average age range of 47 years, and provided care almost 24 hours per day. The elderly had been sick for less than a year on average and showed some degree of partial dependence. Based on the results of the Pearson correlation test, the value of Sig. 0.000 < 0.05 was obtained. Furthermore, the direction of the positive relationship can be seen from the sign of the coefficient (Pearson’s correlation of 0.759), which means that the higher the fatigue, the higher the stress level. Conclusion: These results are expected to be the basic data for future research and should be considered hospitals regarding care for the elderly. This can reduce the impact of the stress on the caregivers’ which can affect the quality of care provided.